Analysis of Chinese Consumers’ Nutrition Facts Table Use Behavior Based on Knowledge-Attitude-Practice Model - Zeying Huang (MDPI AG, 2021)
The nutrition facts table is a nutrition labeling tool designed to help consumers understand the nutritional content of food and make informed food choices. However, the utilization rate of the nutrition facts table has been low in China since its introduction in 2013. This study employed structural equation modeling to investigate consumers’ knowledge, attitudes, and practices related to the nutrition facts table by using an online survey of 930 valid samples from 31 provinces in China based on the knowledge, attitude, practice (KAP) model. The analysis revealed that most respondents had a positive attitude, but not a good level of knowledge or practice in their use of the labeling. Respondents’ knowledge about the nutrition facts table directly affected their attitude, through which it could then affect their practice, whereas knowledge played an indirect role in nutrition labeling use. The results confirmed that the KAP model is suitable for explaining consumers’ use of nutrition labels in China, and that the first step to promoting labeling usage is to enrich consumers’ knowledge on the nutrition facts table.